2007
DOI: 10.1007/s10815-007-9116-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of c-DNA microarray analysis of gene expression between eutopic endometrium and ectopic endometrium (endometriosis)

Abstract: According to our c-DNA analysis some differentially expressed genes may be involved in the pathogenesis of endometriosis. An imbalance in the genes responsible for the reproductive process may lead to a decrease in embryo implantation in patients with endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 36 publications
(37 reference statements)
2
32
0
1
Order By: Relevance
“…According to the onset type, BE is defined as ‘primary’ or ‘secondary’: (1) primary BE is a spontaneously occurring disease, diagnosed in 11% of overall patients diagnosed with DIE [18,19,20,21,22,23,24,25,26,27], while (2) secondary BE is defined as an iatrogenic lesion, occurring after pelvic surgery, such as cesarean delivery or hysterectomy [18,19,20,21,22,23,24,25,26,27]. Up to 50% of patients with BE have a history of past pelvic surgery [13].…”
Section: Resultsmentioning
confidence: 99%
“…According to the onset type, BE is defined as ‘primary’ or ‘secondary’: (1) primary BE is a spontaneously occurring disease, diagnosed in 11% of overall patients diagnosed with DIE [18,19,20,21,22,23,24,25,26,27], while (2) secondary BE is defined as an iatrogenic lesion, occurring after pelvic surgery, such as cesarean delivery or hysterectomy [18,19,20,21,22,23,24,25,26,27]. Up to 50% of patients with BE have a history of past pelvic surgery [13].…”
Section: Resultsmentioning
confidence: 99%
“…11 So far 10 large-scale microarray-based gene expression analysis comparing endometriosis lesions with eutopic endometrium from women with endometriosis have been performed, including the present study (Table 1). [31][32][33][34][35][36][37][38][39] However, there is no study to date which has performed a large-scale gene expression microarray analyses with greater numbers of whole peritoneal lesions compared with eutopic endometrium and peritoneum in single analyses to examine all cell types and both menstrual cycle phases (Table 1). Additionally, no protein analyses were performed, which confirmed significantly differentially expressed genes in the same patient cohort tissues.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 6 of the previous studies analyzed between 1176 and 47 633 genes exclusively from women with ovarian endometriosis in both proliferative and secretory phases. [31][32][33][34]37,38 In another investigation, Eyster et al 39 analyzed a combined cohort of 6 ovarian and 5 peritoneal endometriosis lesions compared to eutopic endometrium on an array of 53 000 probe sets where all but 1 woman with an ovarian endometriosis were in the proliferative phase. Another microarray study identified 19.3% differentially expressed genes from 4684 genes specifically in epithelial cells microdissected from lesions and eutopic endometrium from women with both ovarian and peritoneal endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Softwares used to perform absolute and comparison analysis vary greatly among studies. Although most of the studies simply compared genes increased or decreased in a certain fold, 31,32,35 other studies have used elaborate modeling that included the interaction between the tissue type, menstrual phase, and lesion location. 33 Moreover, hierarchical cluster analysis was performed using very different tools.…”
Section: Limits Of the Gene Expression Studiesmentioning
confidence: 99%
“…Interestingly, this study correlated the methylation patterns with previously validated gene expression data. 35 In general, the methylation level in the promoter regions was not linked to the expression levels of nearby genes, except for 35 genes. Among genes found hypomethylated and upregulated in ovarian endometrioma compared to eutopic endometrium were scavenger receptor class B, member 1, phospholipase D2, cystathionine-b-synthase, and Fas apoptotic inhibitory molecule 3.…”
mentioning
confidence: 95%